Novel 2R3T and 2R2T parallel mechanisms with high rotational capability. Issue 2 (21st July 2015) - Wang, Congzhe; Fang, Yuefa; Fang, Hairong
SUMMARY: Large rotational angles about two axes for parallel mechanisms (PMs) with two rotational and three translational (2R3T) degrees of freedom (DOFs) or two rotational and two translational (2R2T) DOFs are demanded in some industries, such as parallel machine tools and multi-axis 3D printing. To address the problem, this paper focuses on the structural synthesis of new 2R3T and 2R2T PMs with high rotational capability. First, two new moving platforms are proposed based on the concepts of decoupled and configurable design. By means of the proposed platforms and Lie group theory, a series of 2R2T and 2R3T PMs are synthesized. Then the inverse kinematics and velocity relationship of one of the synthesized 2R3T PMs are presented. Finally, the rotational capability of the same 2R3T PM is analyzed. The result shows that by means of actuation redundancy, the studied 2R3T PM indeed possesses the high rotational capability about two axes, even though interferences and singularities are taken into consideration.